Parents' hesitation about getting their children vaccinated against COVID-19 in Japan - Takeshi Yoda; Hironobu Katsuyama (Taylor & Francis Group, 2021)
Given the urgent global need for vaccinating individuals of all ages against the COVID-19 pandemic, understanding the extent and reasons for parents' willingness to get their children vaccinated is important. This study used an internet-based questionnaire survey to determine parents' willingness to get their children (0 to 15 years) vaccinated in Japan and was conducted in April 2021 before COVID-19 vaccination for children began. Socio-demographic information, information about parents' willingness to get children vaccinated, reasons for their responses, and parents' willingness to get themselves vaccinated were obtained. Descriptive statistics were used to evaluate parents' willingness to get children vaccinated based on the other variables. Logistic regression analyses were conducted to identify the characteristics of parents who indicated willingness to get their children vaccinated and to identify the reasons for vaccine willingness. Of the 1100 respondents, 472 were willing to get children vaccinated, 470 were not sure, and 158 did not want to get children vaccinated. Considerable differences were found in the willingness to get children vaccinated across gender, age groups, occupation, annual income, respondent's academic background, and respondent's willingness to get COVID-19 vaccination for themselves. Reasons for being unsure about the vaccination included the vaccine's potential side effects (84.9%), uncertainty about vaccine safety (54.7%), and not trusting vaccine efficiency (25.7%). Parents' willingness to get the COVID-19 vaccine for themselves was a significant factor for their willingness to get children vaccinated after adjusting all other factors. The study recommends disseminating more and correct information to the public to increase vaccine willingness.